Advertising for people who don't like advertising. - Kesselkramer, ....- (London : Laurence King Publishing, 2012)
Advertising for People Who Don't Like Advertising by KesselsKramer is a new book published by Laurence King. It is partly a creative handbook and partly a hunt to find new ways to think about communications. Together with creative people it admires, KesselsKramer goes in search of ideas that might help people like ads, instead of zapping them into oblivion. On the way, they consider a potted history of the business, ways of working that KesselsKramer aspires to embody, and the future of an ever-fragmenting industry. The book is intended for anyone who's ever questioned the business of communications. Its aim is to reach beyond the advertising and marketing sectors and engage with a non-specialist audience, and at students considering communications. KesselsKramer hopes to create advertising that's both truthful and ironic. Starting in 1996, the agency has busied itself with creative projects including fashion collections, music videos, films, exhibitions and book publishing. The agency's thoughts on commercial creativity are the subject of this book and the accompanying blog dontlikeadvertising.com. As well as KesselsKramer's observations, the book includes interviews with Alex Bogusky, Stefan Sagmeister, Erik Kessels, Steve Henry, Anthony Burrill, Hans Aarsman and Mark Fenske.
Keywords: Advertenties